Segmenting Speech: The Role of Resyllabification in Spanish Phonology - Iván Andreu Rascón (Languages)
Humans segment speech naturally based on the transitional probabilities between linguistic elements. For bilingual speakers navigating between a first (L1) and a second language (L2), L1 knowledge can influence their perception, leading to transfer effects based on phonological similarities or differences. Specifically, in Spanish, resyllabification occurs when consonants at the end of a syllable or word boundary are repositioned as the onset of the subsequent syllable. While the process can lead to ambiguities in perception, current academic discussions debate the duration of canonical and resyllabified productions. However, the role of bilingualism in the visual perception of syllable and word segmentation remains unknown to date. The present study explores the use of bilingual skills in the perception of articulatory movements and visual cues in speech perception, addressing the gap in the literature regarding the visibility of syllable pauses in lipreading. The participants in this study, 80 native Spanish speakers and 195 L2 learners, were subjected to audio, visual-only, and audiovisual conditions to assess their segmentation accuracy. The results indicated that both groups could segment speech effectively, with audiovisual cues providing the most significant benefit. Native speakers performed more consistently, while proficiency influenced L2 learners’ accuracy. The results show that aural syllabic segmentation is acquired at early stages of proficiency, while visual syllabic segmentation is acquired at higher levels of proficiency.